Sensing technologies for real time monitoring of water quality - Manjakkal, Libu; Lorenzelli, Leandro; Willander, M. (Hoboken, New Jersey : Wiley-IEEE Press, 2023)
'This book covers a complete set of sensing technologies for water and food (aquaculture) quality monitoring, particularly in relation with the real time monitoring. Section I (Data Quality) is devoted to the introduction and developments of various materials and sensors for water quality monitoring. Section II (Data Gathering) describes the various design of electronics, communication system, packaging and innovative deployment strategies used for remote monitoring for water quality in various atmosphere. Section III (Data Analysis) presents diverse techniques for data analysis of the sensors. This includes artificial intelligence (AI), big data technologies, and machine learning techniques for real-time water quality monitoring and evaluation is desirable for future smart cities. Further, the Section IV (Policy and Management) in the book focuses on sustainable environmental and policy issues, including ways to reduce carbon footprint.'--
Includes index.
Keywords: Water quality -- Measurement; Water quality -- Remote sensing; Intelligent sensors